PENGARUH HASIL BELAJAR MATA PELAJARAN PRODUKTIF, KEMAMPUAN BERKOMUNIKASI DAN SIKAP WIRAUSAHA TERHADAP MINAT WIRAUSAHA PADA SISWA SMK NEGERI SURABAYA - Chabiba, Nur (UNIVERSITAS NEGERI SURABAYA, 2017)
This study aims to determine The Effect of Learning Outcomes On productive lesson, communication ability and Entrepreneurship behaviour Towards Interest of Entrepreneurship by Students at SMKN in Surabaya year 2014 - 2015. The population of as many as 391 and samples with sampling using probability sampling as many as 80. Data collected by questionnaire and documentations. Partially, the Learning Outcomes has no positive and signifficant Effect for Entrepreneurial interest. The conclusion is Communication Skills has a signifficant Influence for Entrepreneurial interest. Entrepreneurship behaviour has a signifficant effect partially on Entrepreneurial Interest. It can be concluded that simultanously, learning outcomes on productive lesson, communication skills, and entrepreneurial behaviour have an influence on the entrepreneurial interest